IMPLEMENTATION OF GOOGLE CLASSROOM AS LEARNING MEDIA IN MTS AL YAKIN PUNGPUNGAN - Sahri (Al Ulya: Jurnal Pendidikan Islam, 2021)
The process of teaching and learning activities should be supported from educators and students through direct or indirect interactions. If there are some students who lack of interest in distance learning, an educator should immediately find a solution for the problem. Learning media during the COVID-19 pandemic has an important role as an effort to succeed learning. So it is hoped that the Google Classroom learning media will be able to increase the interest of the students at Mts Al Yakin. This type of research is a qualitative research. Data collection techniques using observation, interviews and documentation. Based on the research results, the implementation of Google Classroom has a positive effect for both educators and students. There are three activity processes in preparing for the use of Google Classroom, namely planning, implementation and evaluation. In the use of Google Classroom, the students were very enthusiastic and responded with the use of the learning media, even though the learning was distance.